Association Between Flexible Work Arrangement and Sleep Problems Among Paid Workers: Using 6th Korean Working Conditions Survey - Eunseun Han; Yongho Lee; Sanghyuk Lee; Shinhyeong Kim; Seunghon Ham; Wanhyung Lee; Won-Jun Choi; Seong-Kyu Kang (Elsevier, 2024)
Background: As social distancing persists and interest in work-life balance grows, more companies are adopting flexible work policies. While there have been studies on sleep disorders associated with different types of work, such as shift work, research exploring the relationship between flexible work schedules and sleep disorders is still limited, particularly among Korean workers. Methods: We performed a secondary analysis of the 6th Korean Working Conditions Survey, focusing on 31,243 paid workers out of a total of 50,538 participants. We defined flexible workers as those who set their own working hours. Sleep disorders were divided into three categories: 'difficulty falling asleep,' 'frequent waking during sleep,' and 'waking up feeling exhausted and fatigued.' Using scores derived from three specific symptoms, the Minimal Insomnia Symptoms Scale (MISS) was calculated to assess the prevalence of insomnia. We used chi-square tests to analyze demographic and job-related differences. A multivariate logistic regression analysis was employed to identify any relationship between flexible work schedules and sleep disorders. Results: Significant differences were found between flexible and non-flexible workers regarding age, income level, education level, and job type. Flexible workers reported sleep-related symptoms significantly more often. The odds ratio for insomnia was 1.40 (95% CI 1.21-1.61). For males, the odds ratio was 1.68 (1.36-2.08). Conclusion: This study establishes a correlation between flexible work schedules and sleep disorders among Korean salaried workers. Potential causes could include changes in circadian rhythm, increased work demands, and extended working hours. To precisely determine causality and associated diseases, further research is required.